Piezoelectric nanogenerators synthesized using KNbO3 nanowires with various crystal structures - Joung, Mi-Ri; Xu, Haibo; Seo, In-Tae; Kim, Dae-Hyeon; Hur, Joon; Nahm, Sahn; Kang, Chong-Yun; Yoon, Seok-Jin; Park, Hyun-Min (ROYAL SOC CHEMISTRY, 2014)
KNbO3 (KN) nanowires having a tetragonal structure or a polymorphic phase boundary (PPB) structure, which contains both tetragonal (P4mm) and orthorhombic (Amm2) structures, are formed at low temperatures. The presence of tetragonal and PPB KN nanowires is attributed to the existence of OH- and H2O defects. Further, the tetragonal and PPB KN nanowires change to orthorhombic KN nanowires in the temperature range between 300 and 400 degrees C owing to desorption of the lattice hydroxyl group. A composite consisting of polydimethylsiloxane (PDMS) and KN nanowires having a PPB structure shows large dielectric constant and low dielectric loss values of 9.2 and 0.5%, respectively, at 100 kHz. Moreover, a nanogenerator (NG) synthesized using the PPB KN nanowires exhibits the largest output voltage and current among NGs synthesized using the tetragonal or orthorhombic KN nanowires. In particular, the NG containing 0.7 g of PPB KN nanowires shows an output voltage of 10.5 V and an output current of 1.3 mu A; these values are among the highest ever reported for NGs synthesized using a lead-free composite. In addition, this NG exhibited the maximum output power and energy conversion efficiency, which were 4.5 mu W and 0.9%, respectively, for an external load of 1.0 M Omega.
Keywords: TITANATE FINE PARTICLES; NANOCOMPOSITE GENERATOR; LATTICE-DEFECTS; HYDROXYL GROUP